Determination of Maximum Tolerated Dosage of Huang Lian in Mice and its Effect of Intestinal Lactobacillus Population - Chong, Janice Lee Ching (2015)
Huang Lian also known as Rhizoma Coptidis is a dried rhizome of Coptis chinensis which belonged to the Genus Coptis and family of Ranunculaceae. It is used to clear heat and dries Dampness in Traditional Chinese Medicine. Xiang Sha Liu Jun Zhi Tang is a formula decoction used to tonify the Spleen and Stomach and improve the digestive functions. Lactobacillus is an anaerobic bacterium that belonged to the order of lactic acid bacteria (LAB). It is categorized as probiotics which commercially acts as a treatment for diarrhea, indigestion, urinary tract infections and enhancing immunity. Thus the objectives of this study are to determine the maximum tolerated dosage of Huang Lian in mice and analyses its impact on Lactobacillus population with and without XSLJZT. In this experiment, 35 mice are divided into 7 groups with 5 mice each group. Three groups received Huang Lian with the dosage raging from 65mg/kg, 250mg/kg and 500mg/kg respectively while another 3 groups received Huang Lian as described previously combined with 50mg/kg of XSLJZT. The control group of mice was fed with the same volume of saline. The weights of the mice were recorded weekly while XSLJZT significantly increase the weight of the mice during the duration of 28 days. In conclusion, Huang Lian generally inhibit the Lactobacillus while has little effect on the weight of mice.